Pengaruh latihan killer pass dan pass combination terhadap ketepatan passing (passing accuracy) dalam permainan sepakbola pada atlet usia 10-13 tahun di klub ps. tulen lombok timur tahun 2023 - Zen Ali; Mujriah; Sukarman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The aim of this study is to increase passing accuracy by using the Killer Pass (X1) and Pass Combination X2 exercises on athletes aged 10-13 years at Club PS Tulen East Lombok in 2023.The method used in this study was a quasi-experimental